Isolation, screening and selection of xylanase producing thermophilic fungi from Raipur - PARIHAR, PREETI SINGH (Research in Biotechnology, 2015)
In the present study, isolation, screening and selection of xylanase producing thermophilic fungi from soil of Raipur was studied. A total of 55 fungal isolates were isolated and screened for xylanase activity by standard plate assay method and activity of xylanase was determined by estimating the amount of released reducing sugar xylose in culture filtrates. Based on screening methods, 18 isolates with higher xylanase activity were selected for studying effect of temperature i.e. 25, 35, 45, 50, 55, 60, 65oC on their mycelial biomass production and for studying percent coagulation of protein at 50oC at different intervals of time. Five isolates namely Chrysosporium tropicum NFCCI 2531, Malbranchea cinnamomea MTCC 11894, Aspergillus fumigatus NFCCI 2532, Aspergillus terrus NFCCI 2533 and Emericella nidulans NFCCI2538 showed maximum biomass production at 45oC (0.19 to 0.32g/100ml/10days) and minimum protein coagulation at 50oC (14% to 25%). Keywords: Thermophilic fungi, screening, xylanase, temperature biomass, protein coagulation, reducing sugar, xylose.